Perceived Causes of Students’ Poor Performance in Mathematics: A Case Study at Ba and Tavua Secondary Schools - Chand, Samlesh; Chaudhary, Kaylash; Prasad, Avinesh; Chand, Vishal (Frontiers in Applied Mathematics and Statistics, 2021)
Poor achievement in mathematics is an issue of great concern for many countries across the globe. Fiji is one of the countries in the South Pacific experiencing the same trends, pressures and concerns. The national results for mathematics, especially in Fiji Year 12 Certificate Examination (FY12CE) and Fiji Year 13 Certificate Examination (FY13CE) for the past few years had been low. It has become a concern among politicians, teachers, parents, educational experts and other stakeholders. Seven secondary schools were randomly selected from the western part of Fiji for the descriptive study. Student, teacher and curriculum factors were the focus of the study. The target population was 201 respondents which comprised of 171 students, 16 mathematics teachers, 7 department heads and 7 school heads. The data was collected using questionnaires, interviews and student-focus group discussions. The findings revealed that students’ negative attitude and perception towards mathematics and ineffective mathematics curriculum at the senior grades of secondary schools were the factors found to be most significantly affecting the students’ achievement in mathematics. The study further revealed that many of the primary school teachers lacked potential and competence to teach mathematics at primary school levels which were one of the factors that contributed significantly towards students’ lack of interest and students’ poor achievement at both the upper and lower secondary grades. Based on the findings, the following recommendations were made; mathematics curriculum for year 12 and 13 need to be reviewed, all stakeholders including senior mathematics teachers and heads of department to be part of the consultation process in regards to any review and amendments in the school curriculum, new competency standards for recruiting students in primary teaching, content focussed teacher training for primary school teachers to teach specialised subjects in primary schools, regular in-service training for both primary and secondary school teachers for quality and professional development of mathematics teachers and review of the salary structure to attract qualified and experienced graduates in the teaching profession.